Driving the development of energy communities in Colombia: challenges and opportunities for a decentralized energy transition - María Fernanda Medina-Reyes; Juan Gabriel Fajardo-Cuadro; Juan Carlos Martinez-Santos (Revista Hábitat Sustentable)
Energy communities represent a transformative paradigm for democratizing access to renewable energy, decentralizing power systems, and fostering economic sustainability. This study analyzes their global development, with an emphasis on developing countries such as Colombia. The research employs a systematic literature review in Scopus and a keyword co‑occurrence analysis to identify trends; in addition, Colombian regulatory documents were examined to contextualize the findings. The discussion addresses distributed generation, peer‑to‑peer (P2P) energy trading, and regulatory frameworks that drive local energy transitions. Although the opportunities are significant in Colombia, challenges persist in infrastructure, regulation, and social acceptance, particularly in the Caribbean region. The article proposes context‑specific strategies from international experiences to overcome these barriers and consolidate decentralized energy systems that accelerate the country’s energy transition and sustainable development.